2003
DOI: 10.2174/1389557033487917
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Natural and Modified Betulinic, Ursolic and Echinocystic Acid Derivatives as Potential Antitumor and Anti-HIV Agents

Abstract: The aim of this review is to update current knowledge on the betulinic, ursolic and echinocystic acids and their natural and semisynthetic analogs, focussing on their cytotoxic and anti-HIV activities. Then, the last results of the authors' team on unusual semisynthetic derivatives of these triterpenoids will be presented in order to establish structure/activity relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
56
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 0 publications
0
56
0
1
Order By: Relevance
“…OA, UA and their derivatives efficiently inhibit the development of several viruses including HIV. The mechanism of their antiviral activity is already partially resolved, which should permit the therapeutic use of these compounds in the near future [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…OA, UA and their derivatives efficiently inhibit the development of several viruses including HIV. The mechanism of their antiviral activity is already partially resolved, which should permit the therapeutic use of these compounds in the near future [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This class of natural products and their derivatives have been reported to have interesting biological activities, such as anti-HIV, 6,7) antiplasmodial 8,9) and cytotoxic activities. 10,11) Previous investigations have shown that triterpenes also exhibit moderate to high in vitro antimycobacterial activity against M. tuberculosis. [12][13][14] It was reported 12) that betulinic acid (1) was more active than its C-3 epimer, epi-betulinic acid.…”
mentioning
confidence: 99%
“…A major breakthrough occurred 2 years later, when betulinic acid, dihydrobetulinic acid, and platanic acid were shown to be potent and moderately selective HIV inhibitors and that, among various betulinic acid derivatives esterified at C3, the hemisuccinate retained similar potency (Fujioka et al 1994). This led to the development of the extremely potent 3-O-(3 0 ,3 0 -dimethylsuccinyl)betulinic acid, which inhibited HIV replication with EC 50 \ 0.35 nM and a selectivity index of 20,000 (Hashimoto et al 1997) (Bevirimat,, and which is now in Phase II clinical studies: Two important reviews published just before the period we are covering are those of Sun et al (2003) and Baglin et al (2003), the latter concentrating on triterpenoids and more specifically betulinic, ursolic and echinocystic acid derivatives. A short paper on the HIV-1 antiviral activity of betulinic acid derivatives is one by Aiken and Chen (2005).…”
Section: Introductionmentioning
confidence: 99%